A Literatura de Massa como elemento catalisador da promoção do letramento literário no ensino médio - Flávio Amorim da Rocha (2018)
This research project aims at rethinking the role of the school towards the formation of literary readers in high school considering the changes through which society, as well as the written words, have been trough in what comes to technology and evolution of the means of dissemination of the literary art. Our starting point is the fact that literature nowadays is presented in a multimodal identity and it is directed to a community of readers who are more and more influenced by visual stimuli. Thus, having as theoretical foundation discussions about the concepts of literacy, literary literacy, reception theory, the effect theory and the dialogic characteristic of language, based on Bakhtin’s studies, we propose an analysis of the reading process of “mass literature” performed by students from Campo Grande Campus of Federal Institution of Education, Science and Technology of Mato Grsso do Sul. We have made considerations about vocational schools as our research locus and the role literature can have in institutions with these characteristics. Data analysis will be then presented in three parts. The first one comprehends a preparation meeting for the exhibition of the movie Hunger Games and the discussions originated by the movie and by the book written by Suzanne Collins. Afterwards, discursive interactions that happened during the discussion will be analyzed and, finally, the reports written by our research subjects at the end of our project interventions will be presented. We could observe, in the end of the process, that schools, as an agency that promotes different kinds of literacy, in order to promote more effective literary literacy practices, needs to consider beyond canonical literature and focus on the reading experiences brought by students to the classroom. We have realized through students’ discursive interactions with the school community in which they are the presence of other discourses that make up their own when they talk about literary masterpieces destined to what is called “mass”, suggesting that institutions, while power holders, tend to inhibit speeches about the literature that is undervalued by them. As a conclusion we point at the appearance of a new kind of reader, which we will refer to as convergence culture reader. This reader moves easily among different forms of literary expression in its multi modes of semiotic representation thus needing a space for dialogue and identity assertion so that their potentials can be fully developed. We believe that it is the role of the school to provide these spaces, defending the holistic formation of the subjects entrusted to it.